Mast cell leukemia (MCL): Clinico-pathologic and molecular features and survival outcome. (August 2017) - Jain, Preetesh; Wang, Sa; Patel, Keyur P.; Sarwari, Nawid; Cortes, Jorge; Kantarjian, Hagop; Verstovsek, Srdan
Highlights: Mast cell leukemia is a rare type of systemic mastocytosis with a poor prognosis. There is no standard of care treatment and new therapies are needed. Associated hematologic neoplasm negatively impacts the survival of these patients. Abstract: Mast cell leukemia (MCL) is a very rare subtype of systemic mastocytosis (SM). We have identified 13 such patients (5.9%) among 218 patients with SM seen at our institution between 1994 and 2016. Patients with MCL had poor survival (median 31.6 months); response to various therapies was rare and not durable. Clinical course may be affected by concurrent associated hematologic neoplasm and different genetic profiles. More research is required to decipher this rare and enigmatic SM subtype.